LncRNA HOXC-AS5 Affects the Proliferation, Invasion and Cell Cycle of Ameloblastoma Cells by Acting on the Target Gene HOXC13: LncRNA HOXC-AS5 Affects Ameloblastoma Cells - Li, Jin; Zhang, Bin; Wang, Bingxin; Zhang, Xiaoxiao (Cellular and Molecular Biology, 2022)
Ameloblastoma is an odontogenic tumor that occurs in the oral cavity. This tumor is a benign tumor. Ameloblastoma is very aggressive and easily causes tumor metastasis and postoperative recurrence. Studies have shown that the coding gene RNA is involved in the occurrence and development of a variety of tumors. LncRNA HOXC-AS5 as a member of the RNA family, is regarded as a marker of ameloblastoma, which can interfere with tumor cell changes by regulating and controlling the target gene HOXC13. The purpose of this article is to explore the effect of LncRNA HOXC-AS5 on the proliferation, invasion and cell cycle of ameloblastoma cells by acting on the target gene HOXC13, taking 45 patients with ameloblastoma treated in our hospital as the research object. In patients with ameloblastoma tissue, an overexpression vector was constructed by transfecting LncRNA HOXC-AS5 adenovirus and the expression of LncRNA HOXC-AS5 was reduced by the knock-down method, and the effect of LncRNA HOXC-AS5 overexpression and knock-down on the expression level of the target gene HOXC13 was detected. Using flow cytometry to detect the proliferation, invasion and cell cycle distribution of ameloblastoma cells. The research results show that overexpression of LncRNA HOXC-AS5 can reduce the expression level of the target gene HOXC13 by 18.5%. Meanwhile, the proliferation rate of ameloblastoma cells is reduced by 23.2%, and the cell invasion ability index is (145.8±10.5). Cells in G0/G1 phase account for the ratio 68.3%, which was higher than the knock-down group, and the proportion of S-phase cells was 14.6%, which was lower than the knock-down group. Therefore, it can be seen that LncRNA HOXC-AS5 has an inhibitory effect on the target gene HOXC13. When the expression level of the target gene HOXC13 is reduced, it can reduce the proliferation of ameloblastoma cells, reduce cell invasion ability, and extend the cell division cycle.